Composition the mixed saliva and indicators of deciduous teeth caries and its complications in children (Эндодонтия Today, 2020)
An epidemiological examination of 785 children of Khabarovsk region was carried out. High rates of caries and pulpitis of temporary teeth of 3-8 years old children were identifi ed, a insuffi cient level of dental care for Khabarovsk region from was noted. The leading risk factors for the development of caries and pulpitis, their infl uence on the structure and properties of oral liquid were determined. The results shown a strong inverse correlation r = -0,710 between the intensity of caries and the level of sIgA in oral fl uid. The high values of intensity of caries is associated with a low content of sIgA and reducing the barrier function of secretory immunity in the III degree caries activity. The given researches confi rms the need for treatment and prevention of caries of temporary teeth and its complications considering prognostic criteria aff ecting the condition of oral cavity and indicators of mixed saliva.